(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Today there are varieties of comments prevailing among people who use Plastic and Paper bags for their shopping needs. A few people support Plastic bags with their own justifications and others support Paper bags. This is a hot topic of today and arguments are going up and down to deduce which one is better in terms of environmental impact, but some people abstain from this issue by choosing the other option of going with reusable bags. This exploratory study is attempted to infer the environmental concerns made by these bags. The two common grocery bags of today - Paper & Plastic bags are compared in this study. Two imperative measures - total amount of energy used by a bag to get it manufactured and the amount of pollutants emitted during the manufacturing phase of a bag - are chosen as data for Life Cycle Inventory (LCI). To arrive at a clear state of conclusion with respect to environmental impact made by these two bags, life cycle impact assessment (LCIA) study was accomplished. Evolvement of Life Cycle Assessment (LCA) study from the data available on this context is the crux of this study. The Eco-indicator 99, damage oriented method for LCIA in SIMAPRO 7.1 tool is used to assess the environmental impact made by these two grocery bags. The single score values calculated by the Eco-indicator 99 is considered as a directive to compare the environmental impact made by these and a detailed explanation of results is also dealt with in this paper. As far as the Life cycle energy analysis and amount of pollutants produced from these two bags are concerned, a plastic bag simply scores out a paper bag. The impact assessment results are also in line to support the plastic bags over paper bags. However, this conclusion has been drawn on the basis of the secondary data chosen for LCI and the results provided by the software which also has certain hypotheses and assumptions.